Paleogeographic boundary in the evolution of the Pucara Basin (Triassic-Liassic) and the Arequipa basin (Lias-Dogger): an inheritance of the block accreted during the Mesoproterozoic - Carlotto Caillaux, Víctor Santiago (2009)
páginas 50-52.